Case Report: An Ulceration With a Stalactite Appearance on the Index Finger - Zhang, Liangliang; Dai, Yalan; Lin, Mengting; Xu, Qiuyun; Lin, Tingting; Gong, Ting; Cheng, Bo; Ji, Chao; Cai, Donghua (Frontiers in Medicine, 2022)
Proteus mirabilis, the most widespread species of all Proteus spp. bacteria, is proven to be one of the most universal pathogens in chronic wounds. In this case, a woman in her 40s consulted a physician about an asymptomatic ulceration with a stalactite appearance at the distal end of the index finger after she was exposed to a needle when vaccinating chickens. The patient did not response to ceftazidime. Physical examination revealed a well-demarcated violescent ulceration with a stalactite appearance at the distal end of the index finger. A biopsy of the lesion showed dense infiltration of multinucleated giant cells, histiocytes, and lymphocytes in the dermis. The result of metagenomics next-generation sequencing (NGS) showed 306 unique sequence reads of P. mirabilis, covering 33.49% of the nucleotide sequences. The pathogen was identified as P. mirabilis, which was resistant to ceftazidime. The patient was treated with ciprofloxacin hydrochloride and improved considerably. This case reported a distinctive cutaneous lesion of P. mirabilis on human infection and showed a successful use of NGS in P. mirabilis.